1979
DOI: 10.1111/j.1476-5381.1979.tb08672.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiovascular Pharmacology of 7‐propyl‐theophylline‐dopamine (D4975); Comparison With Dopamine and Dobutamine

Abstract: I The effects of a newly developed dopamine-xanthine derivative, 7-propyl-theophylline-dopamine (D4975), have been examined in cats anaesthetized with sodium pentobarbitone. When administered intravenously (in doses as low as 0.5 to 1.0 tg/kg) it increased systemic arterial pressure, left ventricular (LV) dP/dt,,,x, dP/dt at fixed ventricular isovolumic pressures and cardiac output. Heart rate effects were minimal.2 D4975 was about 5 times more active than dopamine or dobutamine in elevating LV dP/dt,... or dP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Dobutamine increases cardiac output and elevates pulmonary artery pressure. 45,46 Our results show that dobutamine increased CO and mPAP in a dose-dependent manner ͑Figure 7͒. Analysis of the dobutamine data indicates that FDPM-derived ͓TotHb͔ and S t O 2 are statistically correlated with dobutaminemediated changes in CO.…”
Section: Discussionmentioning
confidence: 72%
“…Dobutamine increases cardiac output and elevates pulmonary artery pressure. 45,46 Our results show that dobutamine increased CO and mPAP in a dose-dependent manner ͑Figure 7͒. Analysis of the dobutamine data indicates that FDPM-derived ͓TotHb͔ and S t O 2 are statistically correlated with dobutaminemediated changes in CO.…”
Section: Discussionmentioning
confidence: 72%
“…In the study reported here, there was a 17-fold difference between concentrations measured in 2 cats during an infusion rate of 5 μg/kg/min. Dobutamine has been used in a number of studies, [15][16][17] and in 2 studies, 18,19 dobutamine was used in cats anesthetized with inhalants. In cats anesthetized with pentobarbital, dobutamine increased contractility without increasing heart rate or blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, elimination of amrinone follows first-order kinetics with a half-life of 2.6 h.123 The synthesis of amrinone labeled with 14C at C-3 has been reported. lz4 Win 47203 has been described as an analog of amrinone which is 10-30 times more potent than amrinone, with a therapeutic index of 100 [4,5-blpyridines, AR-L57 CL and AR-LlOo BS, were also studied. AR-L57 CL is inactive orally, presumably due t o its low solubility a t physiological pH.lZ7 Likewise, AR-Lroo BS was not active orally, which was attributed t o rapid metabolism and a slow absorption rate.…”
Section: Dopamine and Derivativesmentioning
confidence: 99%